(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2025)
The article analyzes innovative approaches to integrating education and production within the vocational training system. It emphasizes the necessity of harmonizing theoretical learning with practical experience in response to the rapidly changing demands of the labor market. The research highlights the pedagogical significance of dual education, industry-university partnerships, competency-based training modules, and digital technologies as effective mechanisms for ensuring the readiness of future specialists for professional activity. International experiences are examined alongside national practices, providing a comparative framework for improving the integration process. The paper concludes with recommendations for optimizing the interaction between vocational education institutions and industrial enterprises to enhance the quality and competitiveness of graduates.